Quantitative technoeconomic assessment of alumina extraction from aluminium dross: Process efficiency and cost-benefit analysis - Yeoh, Yuan Xin; Noor Intan Shafinas, Muhammad; Kittappa, Shanmuga; Ramalingam, Malarvili; Mohamad Jamil Arif, Mansor; Sumaiya, Zainal Abidin (Springer Nature, 2025)
Managing aluminum dross (AD) is essential due to its adverse impact on the environment. While utilizing AD in alumina production has gained attention, its economic sustainability evaluations remain inadequate despite a large amount of laboratory-scale work being published. Therefore, this study aims to assess the economic impact on an industrial-scale alumina production plant from AD in five scenarios using Aspen Plus simulation and technoeconomic analysis (TEA) based on previous experimental work utilizing the leaching-precipitation technique. The objective of this study is to evaluate different aluminum contents in AD and the number of leaching stages via production scale-up simulation and TEA. Simulation results showed a 10.2% variance in yield compared to experimental work, with consistent aluminum purity. Economic scale analysis suggested a batch size of 94 kg as the most cost-effective minimum selling price (MSP) for alumina, priced at 175.23 USD/kg based on Scenario AD-A (90.98 wt% Al). Discounted cash flow analysis identified 165.59 USD/kg as the lowest MSP for alumina, considering 90.98 wt% Al in AD and the two-stage leaching method. Sensitivity analysis revealed yield and annual batch number as key determinants affecting MSP. The study concludes that a circular economy for AD is feasible and economically viable, suggesting AD as an alternative resource, conserving primary resources for future use.